2000
DOI: 10.1094/pdis.2000.84.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Seed Treatments, Bactericides, and Cultivars on Bacterial Leaf Spot of Lettuce Caused by Xanthomonas campestris pv. vitians

Abstract: As a part of a broader program for management of bacterial leaf spot, the effects of lettuce-seed treatments, greenhouse application of bactericides, and cultivars were evaluated. Seed artificially inoculated with Xanthomonas campestris pv. vitians was treated with bactericides or heat treated and evaluated for the incidence of contaminated seed and seed germination. Seed soaked in 1% sodium hypochlorite for 5 and 20 min had an incidence of contaminated seed of less than 10%. Dry-heat (1 h), hot-water (50°C, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
3
36
1
Order By: Relevance
“…Klement et al (1990) stated that the use of resistant variety for the disease control was the most effective. Earlier findings by Macapuguay and Mnzaya (1988), Sharma et al (1997) and Carisse et al (2000) also showed that planting of a few selected varieties could control or at least reduce the infection in the field.…”
Section: Varietal Resistant Evaluationmentioning
confidence: 84%
“…Klement et al (1990) stated that the use of resistant variety for the disease control was the most effective. Earlier findings by Macapuguay and Mnzaya (1988), Sharma et al (1997) and Carisse et al (2000) also showed that planting of a few selected varieties could control or at least reduce the infection in the field.…”
Section: Varietal Resistant Evaluationmentioning
confidence: 84%
“…The most efficient treatment was 1% of sodium hypochlorite for a soaking time of 5 to 20 min. However, treatments using dry heat or hot water for more than 1 h reduced significantly the seed germination as compared to the untreated seeds (Carisse et al 1999).…”
Section: Seed Treatmentsmentioning
confidence: 82%
“…For instance, in Butterheads, the cultivar Bella Green was highly susceptible and the cultivar Optima showed a low disease severity. Nevertheless, symptoms of BLSL were observed in ail cultivars tested, but the green leaf types were the least susceptible (Carisse et al 1999).…”
Section: Susceptibility Of Cultivarsmentioning
confidence: 91%
See 1 more Smart Citation
“…Application of copper-based fungicides is now the main method of olive leaf spot control in Tunisia and other olive growing countries. However, although there is a lower risk of pathogens developing resistance to copperbased fungicides since they have multi-site activity, some cases of resistance have been reported in bacterial diseases (Vanneste et al 2003;Carisse et al 2000). Washington et al (1992) have reported that copper hydroxide has been ineffective on grey mould of strawberries.…”
Section: Introductionmentioning
confidence: 99%